Employees' Perception of CSR Affecting Employer Brand, Brand Image, and Corporate Reputation - Ozcan, Fatih; Elçi, Meral (Sage Publications Inc, 2020)
Employees are one of the most important factors in business. Therefore, enterprises should account for the expectations of employees, particularly their perception of the enterprise, and their behavior. This study investigates the importance of employees' perceived corporate social responsibility (CSR) and also examines the potential role of predicting employer brand, brand image, and corporate reputation. The study's participants comprise employees working in different departments of various corporations. A total of 559 surveys were collected from randomly sampled company employees working in small and medium-sized enterprises (SMEs) in Turkey, and the responses were analyzed using component-based least squares modeling. The model was analyzed and validated by Smart partial least squares software. Employee-oriented CSR activities have a positive effect on employer brand and brand image perceptions among employees in SMEs. Perceived corporate reputation mediates this relationship.
Keywords: corporate social responsibility; employer brand; brand image; corporate reputation